Pendampingan Implementasi Marketing Mix Dan Tata Kelola Keuangan Untuk Mengoptimalkan Brand TK Aisyiyah Bustanul Athfal (ABA) Balung - Feti Fatimah; Ibna Kamilia Fiel Afroh; Tria Emilia; Sofia Alifah (Universitas Muhammadiyah Jember, 2026)
Aisyiyah Bustanul Athfa (ABA) Kindergarten in Balung is located in a densely populated residential area and is home to many children aged 4 to 5. However, the number of students attending the school has been dwindling. This is due to the community's lack of confidence in the quality and financial management of the school. Therefore, assistance with the implementation of the marketing mix and financial management through community service activities is needed. The goal of this activity is to optimize the brand, thereby increasing public trust in ABA Kindergarten. This is because ABA Kindergarten Balung is able to optimize its product (curriculum, facilities, flagship programs), price (tuition fees, discounts, packages), location (school location, accessibility, comfort), and promotion (advertising, social media, open events, partnerships). This increased trust can enhance the brand and increase the number of students. The methods used in this community service activity include mentoring, training, program implementation, and ongoing monitoring and evaluation. This community service activity has successfully achieved its main objective, which is to provide training and mentoring on the implementation of the marketing mix and financial governance to optimize the ABA Balung Kindergarten brand. This activity also produced various significant outputs, such as a portfolio document on the implementation of the marketing mix and the ability to prepare financial reports. The high enthusiasm from participants and support from partners demonstrates that this activity has a positive impact and is relevant to the partners' needs.